A Micro Model of the Federal Funds Market - HO, THOMAS S. Y.; SAUNDERS, ANTHONY (Journal of Finance, 1985)
ABSTRACT This paper demonstrates that valuable insights into the determination of Federal funds rates can be gained through modeling the micro‐decisions of market participants. Fed fund demand functions are derived for different bank valuation functions and several implications are discussed. Specifically, it is: (i) possible to rationalize the observation that large banks are net purchasers and small banks net sellers of Fed funds; (ii) to explain the positive spread of Fed funds rates over other short‐term money market rates; and (iii) to link the size of this spread to the Federal Reserve's underlying monetary policy strategy.